Aktivitas Quick On The Draw dalam Tatanan Pembelajaran Kooperatif Ditinjau dari Self Confidence pada Materi Peluang - Maimunah, Siti; Nasution, Sri Purwanti (Universitas Islam Negeri Raden Intan Lampung, 2018)
This study aims to determine the effect of the application of quick on the draw activities in the cooperative learning order to the learners 'outcomes whether there is influence between learners who have self-confidence (high, moderate, low) to learners' learning outcomes, to determine whether there is interaction between quick on the draw activities in the cooperative learning arrangement with self-confidence towards learners' learning outcomes. This type of research is quasi-experimental design. The research design used was posttest only. The research samples used proportionate stratified random sampling technique. The data collection used was the interview method, documentation, test, and questionnaire. Instruments used for data retrieval are an essay-shaped test and questionnaire-shaped statements. Data analysis used a two-way ANOVA test with the unequal cell. The result of the research (1) that there is the influence of quick on the drawing activity in the cooperative learning arrangement to the learning result. (2) that there is influence between learners who have self-confidence (high, medium, low) on learning outcomes. (3) there is no interaction between quick on the draw activities in the cooperative learning order with self-confidence towards the learners' learning outcomes.